ECO FRIENDLY HIGH EARLY STRENGTH SELF COMPACTING CONCRETE USING KAOLIN AND WASTE MARBLE DUST - Candra Latu Mowo; Dian Arumningsih (Jurnal Teknik Sipil dan Arsitektur, 2022)
The growth and development of infrastructure in Indonesia is currently growing very rapidly, and the cement production process produces the second largest amount of carbon dioxide after waste, which plays an important role in the current global warming. Self compacting concrete is one of the biggest innovations in the field of construction, Self compacting concrete is one of the biggest innovations in the construction field, where this concrete has high workability but does not ignore compressive strength. Therefore, new, sustainable materials are needed to replace cement production, but they are also required for the workability required to make self-compacting concrete. Green concrete concept, the use of kaolin, and marble dust waste, can be a solution to replace some cement. This innovation research uses XRF or X-ray fluorescence methods to identify and analyze the constituent elements of self-compacting concrete innovations. In this study, self-compacting concrete was obtained using (marble dust waste) which replaced 15% cement, and kaolin which replaced 10% concrete waste. with the main element calcium oxide (CaO) and containing (SiO) can be used as an additive or partial replacement of cement in the manufacture of concrete and kaolin can be obtained from kaolin mines spread across Indonesia, and waste marble dust can be obtained from marble processing, for information 25% of the mass of marble will be lost in the cutting process obtained from marble companies in Solo Raya, the slump flow test measurement is carried out with reference to according to the rules of SNI 1972-2008 and the workability of self-compacting concrete also meets the required requirements. So it can be concluded that it can be a reference source by utilizing waste in Indonesia, easy to obtain, and effective. Keywords: Self-compacting concrete, waste marble dust, kaolin